Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1001/jamadermatol.2022.2749
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Topical Hypericin Photodynamic Therapy for Early-Stage Cutaneous T-Cell Lymphoma (Mycosis Fungoides)

Abstract: ImportanceGiven that mycosis fungoides−cutaneous T-cell lymphoma (MF/CTCL) is chronic, there is a need for additional therapies with minimal short- and long-term adverse effects. Topical synthetic hypericin ointment, 0.25%, activated with visible light is a novel, nonmutagenic photodynamic therapy (PDT).ObjectivesTo determine the efficacy and safety of topical synthetic hypericin ointment, 0.25%, activated with visible light as a nonmutagenic PDT in early-stage MF/CTCL.Design, Settings, and ParticipantsThis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Patients that received two and three 6-week hypericin-PDT treatment cycles had further improvements in index lesion response rates compared to a single treatment cycle of hypericin-PDT (49% after 3 cycles and 40% after 2 cycles vs 16% after 1 cycle; P < .001). 146 In phone interviews of patients treated with MAL-PDT for Stage 1A or 1B MF refractory to topical chemotherapies, patients reported a higher mean satisfaction score for MAL-PDT compared to topical chemotherapies (6.8 vs 4.8; P = .0271). 147 In addition, the study found that if patients were given a choice, 82% preferred MAL-PDT to topical chemotherapy.…”
Section: Emerging Indicationsmentioning
confidence: 96%
“…Patients that received two and three 6-week hypericin-PDT treatment cycles had further improvements in index lesion response rates compared to a single treatment cycle of hypericin-PDT (49% after 3 cycles and 40% after 2 cycles vs 16% after 1 cycle; P < .001). 146 In phone interviews of patients treated with MAL-PDT for Stage 1A or 1B MF refractory to topical chemotherapies, patients reported a higher mean satisfaction score for MAL-PDT compared to topical chemotherapies (6.8 vs 4.8; P = .0271). 147 In addition, the study found that if patients were given a choice, 82% preferred MAL-PDT to topical chemotherapy.…”
Section: Emerging Indicationsmentioning
confidence: 96%
“…Rook et al conducted a dose escalation of hypericin, showing that 0.25% yielded the best therapeutic response [ 66 ]. The FLASH phase 3 randomized controlled trial (NCT02448381) showed significant efficacy after 6 weeks of treatment in early-stage MF/CTCL [ 67 ]. The study engaged 39 academic and community centers and included 196 patients aged 18 years and older with stage IA, IB, or IIA MF.…”
Section: The Role Of Photodynamic Therapy In Treating Primary Cutaneo...mentioning
confidence: 99%
“…There was a 40% increase in TLRR in patients who received two cycles of the treatment ( p < 0.001). The most-common treatment-related adverse events (AEs) were mild local skin reactions, and no drug-related serious AEs were reported [ 67 ]. NCT05380635 further explored the safety of the HyBryte™ (0.25% hypericin) ointment by monitoring the blood level and changes of the electrocardiograms, for which the result was not posted on the website.…”
Section: The Role Of Photodynamic Therapy In Treating Primary Cutaneo...mentioning
confidence: 99%
“…In a FLASH phase 3 randomized clinical trial, a synthetic hypericin ointment (0.25%) obtained a favorable safety profile, and it exhibited satisfying efficiency in early‐stage patch and plaque mycosis fungoides‐cutaneous T‐cell lymphoma (Kim et al, 2022).…”
Section: Pharmacological Effects Of Hypericinmentioning
confidence: 99%